Respuestas

2012-12-20T01:05:23+01:00

f(x) = x^3-6x^2+11x-6 

∫ (x^3-6x^2+11x-6) dx = (x^4/4-6x^3/3+11x/2-6x) + C = (1/4x^4-2x^3+11/2x^2-6x) + C

tiene signo 
. . 0 . . 0 . .0 
- - | + + | - - | + +
. . 1 . . 2 . . 3
http://img812.imageshack.us/img812/2355/…

***********************************
4 . . . . . . . . 1 . . . . . . 2 . . . . . 3 . . . . . . 4
∫ |f(x)| dx = - ∫ f(x) dx + ∫ f(x) dx - ∫ f(x) dx + ∫ f(x) dx =
0 . . . . . . . 0 . . . . . . 1 . . . . . . 2 . . . . . . 3

4
∫ |x^3-6x^2+11x-6| dx =
0

. 1
- ∫ (x^3-6x^2+11x-6) dx +
. 0
. 2
+ ∫ (x^3-6x^2+11x-6) dx +
. 1
. 3
- ∫ (x^3-6x^2+11x-6) dx +
. 2
. 4
+ ∫ (x^3-6x^2+11x-6) dx =
. 3

. . . . . . . . . . . . . . . . . . .1
-(1/4x^4-2x^3+11/2x^2-6x) | +
. . . . . . . . . . . . . . . . . . .0
. . . . . . . . . . . . . . . . . . .2
+(1/4x^4-2x^3+11/2x^2-6x) | +
. . . . . . . . . . . . . . . . . . .1
. . . . . . . . . . . . . . . . . . .3
-(1/4x^4-2x^3+11/2x^2-6x) | +
. . . . . . . . . . . . . . . . . . .2
. . . . . . . . . . . . . . . . . . .4
+(1/4x^4-2x^3+11/2x^2-6x) | = -(-2,25)+0,25-(-025)+2,25 = 5
. . . . . . . . . . . . . . . . . . .3

  • Usuario de Brainly
2012-12-20T01:08:44+01:00
I Did : 5(x-2)+2(x-4)=(2x+3)(x-4)
5x-10+2x-8=2x^2-8x+3x-12
7x-18=2x62-5x-12
7x-18+-2x^2+5x+12=0
12x-6+-2x^2=0
x^2+-6x+3=0
Then I used the quadratic formula and got:
x=6+-2sqrt6/2
x=3=-sqrt6